Scanning FCS, a novel method for three-dimensional particle tracking. (1st October 2003) - Levi, V.; Ruan, Q.; Kis-Petikova, K.; Gratton, E.
Abstract : We describe a novel method to track fluorescent particles in three dimensions with nanometre precision and millisecond time resolution. In this method, we use our two-photon excitation microscope. The galvomotor-driven x – y scanning mirrors allow the laser beam to move repetitively in a circular path with a radius of half the width of the point spread function of the laser. When the fluorescent particle is located within the scanning radius of the laser, the precise position of the particle in the x – x plane can be determined by its fluorescence intensity distribution along the circular scanning path. A z -nanopositioner on the objective was used to change the laser focus at two planes (half width of the point spread function apart). The difference of the fluorescence intensity in the two planes is used to calculate the z -position of the fluorescent particle. The laser beam is allowed to scan multiple circular orbits before it is moved to the other plane, thus improving the signal to noise ratio. With a fast feedback mechanism, the position of the laser beam is directed to the centre of the fluorescent particle, thus allowing us to track a particle in three dimensions. In this contribution we describe some calibration experiments performed to test the three-dimensional tracking capability of our system over a large range.